Thermal Insulating Concrete Tiles - Saeed, Sarkawt Abdul-Rahman; Saeed, Rahman; Shaan, Riyadh Hanna (Sulaimani Journal for Pure and Applied Sciences, 2007)
This paper studies the shape of high-thermal insulating concrete tiles used for roof tiling. The theoretical part consists of a comparison between this invented tiles and ordinary terrazzo tiles. The analysis depends on the values of thermal conductivity of the materials used. The results showed that when these tiles are used for roof tiling, the temperature difference between the outside of roof surface and the inside room can be reduced about (6) times compared with the use of the ordinary terrazzo tiles. In addition, three specimens were fabricated and tested for rupture and absorption tests. The test results showed that, they have a good resistance to the applied test loads, and high resistance to water absorption. The authors believe that the results are remarkable, highly applicable and should be taken into consideration in building constructions.
Keywords: Concrete; Tiles; Thermal insulating